2021
DOI: 10.1051/0004-6361/202141277
|View full text |Cite
|
Sign up to set email alerts
|

A large sub-Neptune transiting the thick-disk M4 V TOI-2406

Abstract: Context. Large sub-Neptunes are uncommon around the coolest stars in the Galaxy and are rarer still around those that are metal-poor. However, owing to the large planet-to-star radius ratio, these planets are highly suitable for atmospheric study via transmission spectroscopy in the infrared, such as with JWST. Aims. Here we report the discovery and validation of a sub-Neptune orbiting the thick-disk, mid-M dwarf star TOI-2406. The star’s low metallicity and the relatively large size and short period of the pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 138 publications
6
14
0
Order By: Relevance
“…The resulting FPP value 0.014 is close to the normal FPP threshold of 0.015 (1.5%) to classify a validated planet (Giacalone et al 2021). Wells et al (2021) found that ground light curves sometimes put a better photometric constraint than the TESS data. We thus rerun the pipeline using the same contrast curve but the SPECULOOS-North/Artemis time-series, which yields a FPP value of 4 × 10 −3 .…”
Section: Statistical Validationsupporting
confidence: 58%
See 1 more Smart Citation
“…The resulting FPP value 0.014 is close to the normal FPP threshold of 0.015 (1.5%) to classify a validated planet (Giacalone et al 2021). Wells et al (2021) found that ground light curves sometimes put a better photometric constraint than the TESS data. We thus rerun the pipeline using the same contrast curve but the SPECULOOS-North/Artemis time-series, which yields a FPP value of 4 × 10 −3 .…”
Section: Statistical Validationsupporting
confidence: 58%
“…Fortunately, the Transiting Exoplanet Survey Satellite (TESS, Ricker et al 2015) is performing an all-sky survey and targets bright nearby stars, providing an exciting opportunity to discover small transiting planets around M dwarfs. The TESS Primary Mission has already yielded the detections of several such systems (e.g., Vanderspek et al 2019;Gan et al 2020;Wells et al 2021;Fukui et al 2021). Some of those planets also have precise mass constraints through spectroscopic measurements thanks to the brightness of their host stars (e.g., Luque et al 2019;Shporer et al 2020;Cloutier et al 2020;Soto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, if we limit the comparison to the 279 confirmed planets around M dwarfs with T eff below 3800 K, only 14 planets have been found so far with orbital periods shorter than 10 days and planetary radii in the range 2.5R ⊕ <R p < 5 R ⊕ . As shown in Figure 12, TOI-1696 b is similar to K2-25 b (Mann et al 2016), K2-320 b(Castro González et al 2020, GJ 1214 b (Charbonneau et al 2009), TOI-269 b (Cointepas et al 2021), and TOI-2406b(Wells et al 2021) in terms of orbital period and radius. In particular, TOI-2406 b appears most similar to TOI-1696 b as it orbits around a mid-M dwarf with an effective temperature of 3100 ± 75, and has a radius of 2.94 ± 0.17 R ⊕ and orbital period of 3.077 days.…”
Section: Statistical Validationmentioning
confidence: 53%
“…In Figure 10 it is clear that larger exoplanets are unusual around cooler stars, and that larger radii exoplanets become even more sparse the cooler the star. Only 10 currently confirmed planets orbit stars with T eff <3500 K while also having a radius >2.8 R ⊕ (Konopacky et al 2010;Leggett et al 2014;Artigau et al 2015;Bakos et al 2020;Castro González et al 2020;Fontanive et al 2020;Stefánsson et al 2020c;Parviainen et al 2021;Wells et al 2021;Zhang et al 2021). Further, only five of these are close to their star, with P orb <100 days.…”
Section: Toi-1696mentioning
confidence: 99%